Long Non-coding RNA MALAT1: A Key Player in Liver Diseases - Lu, Juan; Guo, Jing; Liu, Jun; Mao, Xiaomin; Xu, Kaijin (Frontiers in Medicine, 2022)
Long noncoding RNAs (lncRNAs) exceed 200 nucleotides in length are considered to be involved in both developmental processes and various diseases. Here, we focus on lncRNA MALAT1(metastasis-associated lung adenocarcinoma transcript 1), which was one of the most important lncRNAs in proliferation, apoptosis, and migration. MALAT1 plays a regulatory role in liver diseases, including hepatic fibrosis, liver regeneration, liver cancer, and fatty liver diseases. In the current review, we summarize the latest literature about the function roles of MALAT1 in liver disorders. Probing the regulatory mechanism and cross talk of MALAT1 with other signaling pathways of pathological processes would improve the prognosis, diagnosis of liver diseases, and offer a promising candidate target for therapeutic interventions.